[Molecular analysis of integration sites of the Drosophila retrotransposon burdock.] - Krasnov, A.N.; Okladnova, O.V.; Churikov, N.A. (Genetika, 1999)
Data on molecular analysis of the insertion sites of nine random copies of burdock retrotransposon are presented. The 12-bp consensus sequence of the insertion sites, YNNUTUTUYAYA (Y-pyrimidine; U-purine), was determined. Homology between the burdock sequence and ribosomal genes was revealed. Three copies of this element were located within the region of ribosomal repeats: one copy in the 18S RNA gene, and two copies in the same intergenic spacer region, in the so-called Alu-repeats of Drosophila, in different copies of ribosomal genes.